The Nearctic species of Grzegorzekia Edwards (Diptera: Mycetophilidae) - Fitzgerald, Scott J. (Zootaxa, 2019)
Three Nearctic species of Grzegorzekia Edwards are recognized: G. collaris (Meigen), G. kerri n. sp. and G. quercus n. sp. Species are distinguished from their congeners as well as from the similar species Creagdhubhia mallochorum Chandler and Phoenikiella phoenix (Väisänen). The generic concept of Grzegorzekia is revised to include the new species and a key to males and females of the world species is provided.